2010
DOI: 10.1111/j.1600-0412.2010.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental abruption: epidemiology, risk factors and consequences

Abstract: Placental abruption, classically defined as a premature separation of the placenta before delivery, is one of the leading causes of vaginal bleeding in the second half of pregnancy. Approximately 0.4-1% of pregnancies are complicated by placental abruption. The prevalence is lower in the Nordic countries (0.38-0.51%) compared with the USA (0.6-1.0%). Placental abruption is also one of the most important causes of maternal morbidity and perinatal mortality. Maternal risks include obstetric hemorrhage, need for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
288
4
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(324 citation statements)
references
References 99 publications
(258 reference statements)
16
288
4
16
Order By: Relevance
“…The exact mechanism defining how ascending infection stimulates preterm delivery is still unclear; overproduction of cytokines by activated macrophages was postulated to enhance the synthesis of prostaglandins which act as a direct trigger to initiate labor [28][29][30][31]. Perinatal consequences of ascending infection may also include low birth weight, stillbirth or intrauterine death [14,32]. Our findings confirm that placental inflammation is associated both with a decrease in biometric parameters of the neonate and with higher incidence of preterm birth and stillbirth.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The exact mechanism defining how ascending infection stimulates preterm delivery is still unclear; overproduction of cytokines by activated macrophages was postulated to enhance the synthesis of prostaglandins which act as a direct trigger to initiate labor [28][29][30][31]. Perinatal consequences of ascending infection may also include low birth weight, stillbirth or intrauterine death [14,32]. Our findings confirm that placental inflammation is associated both with a decrease in biometric parameters of the neonate and with higher incidence of preterm birth and stillbirth.…”
Section: Discussionsupporting
confidence: 77%
“…Placental abruption is considered to be a significant independent predictor of preterm birth [14,[32][33][34][35]. Ananth et al [14] showed that placental abruption is associated with a 4-to 6-fold increase in the risk of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between maternal age, parity, previous obstetric history, fetal growth, and other maternal conditions with intrapartum complications such as sentinel events or abnormal CTG has previously been explored. [26][27][28][29] In Locatelli et al used inclusion and exclusion criteria similar to ours in a hospitalbased study of 27 cases and 100 term controls. Intrapartum factors alone were found in 22% of cases and a combination of antepartum and intrapartum factors was identified in an additional 44%.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the duration of infertility is more than twelve months (1). The rate of unexplained infertility varies in different cases and studies but is usually about 10 to 20% (2,3). Unexplained infertility is not an immovable condition, it is a relative inability to conceive, and it is clear that many of these couples may conceive without treatment, but treatment will often fasten the time to conceive (4).…”
Section: Introductionmentioning
confidence: 99%